Intelligence Report on Bafut Area, Bamenda Division, Cameroons Province (Colonial Letters and the Contact of Knowledges, 1935)
This file contains colonial intelligence report, proposals, and geneological tree on Bafut Area, Bamenda Division
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Colonial Intelligence Report; Bafut; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies